Diálogo entre o design de superfície e o design de moda: o caso das padronagens - Silva, Dailene Nogueira da [UNESP] (2015)
This study proposes dialogue between two important aspects of creating and producing clothing: the surface design and the fashion design. To develop a patterned fabric the designer works in two-dimensional field, but this surface became three-dimensional to wapping the body in the garment production, forming a compositional whole, together with the modeling, sewing and finishing. Therefore, is studied the relations between the patterned and clothing, in three stages: a literature review of the subjects involved in the issue, interviews with professionals and finally experiments